Freud: A Very Short Introduction - Storr, Anthony (New York Oxford University Press, 2001)
Sigmund Freud, the founder of psychoanalysis, developed a totally new way of looking at human nature. Only now, with the hindsight of the half-century since his death, can we assess his true legacy to current thought. As an experienced psychiatrist himself, Anthony Storr offers a lucid and objective look at Freud's major theories, evaluating whether they have stood the test of time, and in the process examines Freud himself in light of his own ideas. An excellent introduction to Freud's work, this book will appeal to all those broadly curious about psychoanalysis, psychology, and sociology.
Includes Index and Illustrations.
Keywords: Freud, Sigmund, -- 1856-1939